Strategi Sekolah Dalam Mewujudkan Visi Dan Misi Di Madrasah Ibtidaiyah Wali Songo Asy-Syirbaany Tangerang Selatan - Baroroh, Fatimatul; Malinda, Eva; Mauludi, Rafid; Zahruddin; Maftuhah (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to analyze the strategies used by Madrasah Wali Songo Asy-Syirbaany Madrasah (MI) in realizing the vision and mission of the school. This research uses a qualitative approach with a phenomenological method, to explore how the process of formulating and implementing the vision and mission is carried out. Data collection was conducted through observation, interviews, and document analysis. The research findings show that the formulation of the vision is carried out through an annual working meeting with the participation of teachers, committees and the principal school. The school's vision focuses on fostering the Quran and building a generation that is religious, scientific, cultured, and has noble character. The research results also revealed that there is a periodic revision of the vision to make it relevant to the development of the environment. Although MI Wali Songo Asy-Syirbaany has an excellent program in religious education and literacy, there are also program in religious education and literacy, there are several challenges, such as the limited number of teachers with pesantren backgrounds and ineffective communication with parents. In conclusion, the school strategy in realizing the vision and mission needs to be strengthened through increased participation of all stakeholders and optimization of learning programs.